Suicide thought among children - Tezcan, A.E.; Culha, F.; Karabulut, C.; Namli, M. (My University, 1996)
In this study we aimed to determine the prevalence of the children having suicidal thoughts and identifying the factors influencing this prevalence. The study group consisted of 373 pupils of Elazig Fevzi Cakmak Primary School and their ages were from 9 to 11 years. Depression Scale for Children (DSC) was used to measure the extent of the depression among the children and those who replied 'yes' to question of whether they consider suicide were interviewed and psychiatric evaluations were made. A separate questionnaire developed by ourselves for determining the independent variables of the survey was used together with the DSC. Suicidal thoughts has been observed that 10 (21.7%) of 46 pupils whom intense depressive findings were discovered, and 14 (4.3%) of 327 pupils in whom depression could not be diagnosed, and total 24 (6.4%) of 373 pupils. In conclusion; the suicidal thoughts among the children are mostly accompanied by depressive disorders, although secondary suicidal thoughts resulting from environmental factors without any psychiatric disorders exists.
Keywords: Children; Depression; Suicide